Immunohistochemical analysis of CDw52 antigen expression in non-Hodgkin's lymphomas. - Salisbury, J R (1994)
AIM--To determine the antigen expression of CDw52 using Campath-1 antibodies in a series of non-Hodgkin's lymphomas (NHLs). METHODS--Tissue sections of lymphoma were stained immunohistochemically using rat Campath-1G and humanised Campath-1H with avidin-biotin-peroxidase complex techniques. Fifty-two fresh frozen lymphomas and a further 26 paraffin wax embedded sections were studied. RESULTS--Thirty-seven out of 41 B cell lymphomas were positive with Campath-1H in frozen sections (low grade, 24 of 24; high grade, 13 of 17) as were three out of five T cell lymphomas. Reed-Sternberg cells in six cases of Hodgkin's disease did not react. Eleven out of 16 high grade B cell lymphomas also stained positively with Campath-1G in paraffin wax sections as did five out of 10 T cell lymphomas. CONCLUSIONS--The Campath-1 antibodies showed that CDw52 antigen expression was present in all cases of low grade B cell NHL examined. Immunohistochemical staining in high grade B cell NHL and in T cell NHL was variable. These findings may be relevant to patient selection when considering treatment with Campath-1 antibodies.